1997
DOI: 10.1038/sj.leu.2400722
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FLT4 and its ligand VEGF-C in acute myeloid leukemia

Abstract: mononuclear cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 2 publications
3
74
1
4
Order By: Relevance
“…In agreement with our results, expression of VEGFR-3 has been reported in some hematopoietic and leukemia cells. 62,63 Furthermore, we observed increased densities of peritumoral macrophages in the skin surrounding VEGF-C-transfected melanomas. Enhanced host-tumor defense capabilities by increased recruitment of macrophages may explain the observed growth impediment of VEGF-C-overexpressing melanomas, because increased densities of peritumoral macrophages were correlated with the extent of tumor growth suppression.…”
Section: Discussionmentioning
confidence: 75%
“…In agreement with our results, expression of VEGFR-3 has been reported in some hematopoietic and leukemia cells. 62,63 Furthermore, we observed increased densities of peritumoral macrophages in the skin surrounding VEGF-C-transfected melanomas. Enhanced host-tumor defense capabilities by increased recruitment of macrophages may explain the observed growth impediment of VEGF-C-overexpressing melanomas, because increased densities of peritumoral macrophages were correlated with the extent of tumor growth suppression.…”
Section: Discussionmentioning
confidence: 75%
“…Fielder et al (1997) reported that leukaemic cells expressed VEGF-C in most of the AML patients. Dias et al (2002) found that VEGF-C that was released from the endothelium could induce leukaemic cell proliferation, promote their survival, and protect them from chemotherapy-induced apoptosis.…”
Section: Angio-indexmentioning
confidence: 99%
“…Compared to the levels in the control, increased plasma levels of VEGF-A obtained from peripheral blood (PB) were observed in AML patients (Aguayo et al, 2000(Aguayo et al, , 2002. Elevated VEGF-C expression was reported in patients with prostatic carcinoma and oesophageal squamous cell carcinoma (Tsurusaki et al, 1999;Kitadai et al, 2001) but is controversial with regard to AML patients (Fielder et al, 1997;Dias et al, 2002;Loges et al, 2005). In contrast, decreased VEGF-D expression levels were reported in patients with lung adenocarcinoma and colorectal carcinoma (Niki et al, 2000;Onogawa et al, 2004).…”
mentioning
confidence: 99%
“…VEGF type C, another member of the vascular endothelial growth factor family, is expressed by leukemic blasts in a significant proportion of patients with AML. 33 VEGFR-2 was thought to be exclusively expressed by adult endothelial cells. However, it has recently been shown that VEGFR-2 is present on a subset of primitive hematopoietic stem cells 34 as well as on some leukemic cell lines and isolated blasts from AML patients.…”
Section: Introductionmentioning
confidence: 99%